2020
DOI: 10.3390/coatings10080792
|View full text |Cite
|
Sign up to set email alerts
|

A Fully Inkjet-Printed Strain Sensor Based on Carbon Nanotubes

Abstract: A fully inkjet-printed strain sensor based on carbon nanotubes (CNTs) was fabricated in this study for microstrain and microcrack detection. Carbon nanotubes and silver films were used as the sensing layer and conductive layer, respectively. Inkjet-printed CNTs easily undergo agglomeration due to van der Waals forces between CNTs, resulting in uneven films. The uniformity of CNT film affects the electrical and mechanical properties. Multi-pass printing and pattern rotation provided precise quantities of sensin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 30 publications
(29 reference statements)
2
13
0
Order By: Relevance
“…10 6 µΩ cm for a 10 wt% composition of MWCNTs. Since our reported value is still at least one order of magnitude smaller, we can conclude that the further increase of MWCNT content in our inkjet-printed sensors (25 wt% compared to 10 wt%) results in a lower resistivity and agrees well with the detailed investigation by Yan et al Another reference value is found in the work of Kao et al [26] where they use a commercially available CNT ink (CNT-22, lab311, Korea) for a fully inkjet-printed strain sensor. Unfortunately, the exact composition of the ink is not disclosed and the thickness for a series of samples with different number of passes printed is not given.…”
Section: B Electrical Characterizationsupporting
confidence: 91%
See 2 more Smart Citations
“…10 6 µΩ cm for a 10 wt% composition of MWCNTs. Since our reported value is still at least one order of magnitude smaller, we can conclude that the further increase of MWCNT content in our inkjet-printed sensors (25 wt% compared to 10 wt%) results in a lower resistivity and agrees well with the detailed investigation by Yan et al Another reference value is found in the work of Kao et al [26] where they use a commercially available CNT ink (CNT-22, lab311, Korea) for a fully inkjet-printed strain sensor. Unfortunately, the exact composition of the ink is not disclosed and the thickness for a series of samples with different number of passes printed is not given.…”
Section: B Electrical Characterizationsupporting
confidence: 91%
“…This behaviour should not affect any properties of the device as it occurs only in the first few drops. Similarly, Kao et al [26] report an agglomeration of CNTs at the printing origin due to edge-enhanced evaporation and an overall decrease of CNT density along the printed lines. We do not observe such an extended trend for our printed structures.…”
Section: A Morphology Of Printed Structuresmentioning
confidence: 84%
See 1 more Smart Citation
“…Similar to polymers, certain types of nanomaterials, such as carbon-based allotropes [ 42 , 43 , 44 ] and metallic nanomaterials [ 45 , 46 , 47 ], have been used as processed materials to form sensors. The carbon allotropes include Carbon Nanotubes (CNTs) [ 48 , 49 , 50 ], graphene [ 51 , 52 , 53 ], and graphite [ 54 , 55 , 56 ], while some of the types of metallic nanomaterials are nanoparticles [ 57 , 58 ], nanoribbons [ 59 , 60 ], and nano-beads [ 61 , 62 ].…”
Section: Introductionmentioning
confidence: 99%
“…This caused the researchers to further develop sensors that included flexible materials. The sensors have been devised using extensive printing techniques [ 18 , 19 ] such as screen printing [ 20 , 21 ], inkjet printing [ 22 , 23 ], 3D printing [ 24 , 25 ], offset lithography [ 26 , 27 ], flexography [ 28 , 29 ], and gravure printing [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%